1983
DOI: 10.5014/ajot.37.8.541
|View full text |Cite
|
Sign up to set email alerts
|

Oral Sensorimotor Therapy in the Developmentally Disabled: A Multiple Baseline Study

Abstract: The efficacy of a program of sensorimotor facilitation procedures to improve oral motor function and feeding behaviors in students with severe developmental delay was explored. Four severely handicapped students were administered the oral habilitation program using a multiple baseline across-subjects design with staggered introduction of the treatment. Graphic analysis and the split middle method of trend estimation revealed that one subject evidenced an increase in weight and improved oral motor evaluation as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0
1

Year Published

1985
1985
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 0 publications
1
26
0
1
Order By: Relevance
“…This was apparent, for example, in the indices of postural control, range and control of jaw movement, and control of mastication/swallowing derived from the modified SOMA. Similar observations were made by Ottenbacher et al [31] and Iammatteo et al [25] who remarked that the results of oral-skills training seemed more encouraging for children with lowest ability. Adams [59], in his historical review of the literature on the learning, retention, and transfer of human motor skills, highlighted an early article by Kincaid in 1925 where 24 studies on individual differences and learning were reanalyzed.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…This was apparent, for example, in the indices of postural control, range and control of jaw movement, and control of mastication/swallowing derived from the modified SOMA. Similar observations were made by Ottenbacher et al [31] and Iammatteo et al [25] who remarked that the results of oral-skills training seemed more encouraging for children with lowest ability. Adams [59], in his historical review of the literature on the learning, retention, and transfer of human motor skills, highlighted an early article by Kincaid in 1925 where 24 studies on individual differences and learning were reanalyzed.…”
Section: Discussionsupporting
confidence: 58%
“…Oral-motor function was compared on the basis of performance in discrete motor tasks [21,22], frequency of drooling [23,24], weight of saliva lost from the mouth [25][26][27], or intraoral pressure during swallowing [28]. Attention has also focused on the type and amount of food eaten [29,30], differences in body weight or rate of growth [8,31,32], or meal duration [11,30].…”
mentioning
confidence: 99%
“…36 Efficacy studies have been limited. Ottenbacher et al 37,38 demonstrated no change in oral motor function or weight gain during 9 weeks of sensorimotor treatment in children with severe neurological impairments. Two intervention trials for the efficacy of sensorimotor treatment involved 25 and 35 children (2.5-13 years) with moderate to severe cerebral palsy and undernutrition.…”
Section: Feeding Methods: Evidence-based Reviewmentioning
confidence: 98%
“…Em outra pesquisa (18) , os autores afirmam que o aumento da textura do alimento, tornando-o mais sólido, exige um maior esforço mastigatório, aumentando o tempo de alimentação. Outra pesquisa (19) relata que a persistência do movimento de sucção com a língua nas crianças com PC, além de dificultar a aquisição de movimentos mais sofisticados de língua, quando acompanhado de hiper ou hiposensibilidade oral, também conduz à incapacidade de mastigar e deglutir alimentos. Em estudo (4) realizado com 57 crianças com PC tetraparesia espástica, apenas três deglutiram a consistência alimentar sólida.…”
Section: Discussionunclassified